Examining the Impact of Factors on Firm Value with Corporate Social Responsibility as a Moderator: A Generalized Method of Moments Approach in the Consumer Non-Cyclicals Industry - Pangestuti, Dewi Cahyani; Tri Siswantini; Alfida Aziz; Heni Nastiti (Department of Management, Faculty of Economics and Business, Brawijaya University, 2025)
The non-cyclical consumer sector, which is defined by the production of essential goods, has demonstrated a notable degree of resilience in the face of economic fluctuations. Despite this stability, the dynamics influencing firm value in this sector remain complex. A plethora of literature has been published on topics such as dividend policy, profitability, sales growth, market risk, and inflation. Nevertheless, the role of Corporate Social Responsibility (CSR) as a moderating variable has received less attention. The objective of this study is to address this lacuna by examining the manner in which CSR influences the relationship between these factors and firm value. The objective of the present study is twofold: first, to provide insights into the potential long-term and short-term effects of these variables, and second, to explore the relationship between the variables and the potential effects on the patient's well-being. This study employs the Generalized Method of Moments (GMM) to examine dynamic panel data from 87 companies operating within the Consumer Non-Cyclicals sector and listed on the Indonesia Stock Exchange from 2017 to 2023. The findings of the study demonstrate a positive correlation between profitability and firm value, while market risk and inflation exhibit a negative relationship with firm value. CSR was found to moderate the relationship between profitability, market risk, and inflation but did not moderate the effects of dividend policy or sales growth on firm value. However, its role is context-dependent and does not universally apply to all financial variables.